Integrating Bayesian Inference with Scanning Probe Experiments for Robust Identification of Surface Adsorbate Configurations (Adv. Funct. Mater. 32/2021). (10th August 2021) - Järvi, Jari; Alldritt, Benjamin; Krejčí, Ondřej; Todorović, Milica; Liljeroth, Peter; Rinke, Patrick
Abstract : Bayesian Inference In article number 2010853, Patrick Rinke and co‐workers combine artificial intelligence enhanced ab‐initio structure search with atomic force microscopy simulations (SIM) and experiments (EXP) to detect configurations of bulky 3D adsorbates. Bayesian inference is employed to identify distinct stable adsorption configurations of (1S)‐camphor on the Cu(111) surface, followed by SIM‐EXP image feature matching to fingerprint multiple experimental structures.